Penyesuaian Diri Santri Ditinjau dari Keterampilan Sosial dan Usia - Hasan, Fadilla Rifky; Hertinjung, Wisnu Sri (Universitas Muhammadiyah Metro, 2024)
Islamic boarding schools are places where students learn and live while they complete their education. Students undoubtedly had difficulties in the Islamic boarding school, including the transition process. According to the preliminary evaluation findings at the Assalam Islamic Modern Islamic Boarding School, students' self-adjustment capacity is quite long. 38% of the 150 students at PPMI Assalam reported a more extended adjustment period during their early move, especially students in their first year at Islamic boarding schools. The purpose of this study is to identify the relationship between social skills and students' self-adjustment, as well as to discover age disparities in students' self-adjustment. The first hypothesis in this study is a favorable association between social skills and self-adjustment in students. The second hypothesis is that students' adjustment differs depending on their age. The subjects of this study were Islamic boarding school students from Modern Islam Assalam, and four classes were chosen randomly from a total of 22 courses. From the four completed clusters, 103 students were selected. This study employed a quantitative approach, with questionnaires provided on paper. This study's tools are the self-adjustment scale and the social skills scale. The Anacoval test was used to assess data in this study. The results showed that social skills positively correlated with self-adjustment, and age was not the main predictor of differences in students' self-adjustment.